Antenatal screening for Group B Streptococcus: A diagnostic cohort study - Darbyshire Philip; McDonald Helen M; Hiller Janet E; Crowther Caroline A (BMC Pregnancy and Childbirth, 2005)
Abstract Background A range of strategies have been adopted to prevent early onset Group B Streptococcal (EOGBS) sepsis, as a consequence of Group B Streptococcal (GBS) vertically acquired infection. This study was designed to provide a scientific basis for optimum timing and method of GBS screening in an Australian setting, to determine whether screening for GBS infection at 35–37 weeks gestation has better predictive values for colonisation at birth than screening at 31–33 weeks, to examine the test characteristics of a risk factor strategy and to determine the test characteristics of low vaginal swabs alone compared with a combination of perianal plus low vaginal swabs per colonisation during labour. Methods Consented women received vaginal and perianal swabs at 31–33 weeks gestation, 35–38 weeks gestation and during labour. Swabs were cultured on layered horse blood agar and inoculated into selective broth prior to analysis. Test characteristics were calculated with exact confidence intervals for a high risk strategy and for antenatal screening at 31–33 and 35–37 weeks gestation for vaginal cultures alone, perianal cultures alone and combined low vaginal and perianal cultures. Results The high risk strategy was not informative in predicting GBS status during labour. There is an unequivocal benefit for the identification of women colonised with GBS during labour associated with delaying screening until 36 weeks however the results for method of screening were less definitive with no clear advantage in using a combined low vaginal and perianal swabbing regimen over the use of a low vaginal swab alone. Conclusion This study can contribute to the development of prevention strategies in that it provides clear evidence for optimal timing of swabs. The addition of a perianal swab does not confer clear benefit. The quantification of advantages and disadvantages provided in this study will facilitate communication with clinicians and pregnant women alike.